The Public Life of Abortion and the Making of South Africa's Choice on Termination of Pregnancy Act - Koekemoer, Ronel (Department of Historical Studies, 2023)
This thesis is a study of the making of post-apartheid South Africa's abortion law, the Choice on Termination of Pregnancy Act, 1996. It focusses on how abortion as a public interest issue at the time of SA's transition from apartheid to democracy shaped the arguments, actors and arenas involved in the development of CTOP. This has the broader goal of denaturalising these institutions and evaluating the role of contextual factors in assessing CTOP's institutional legacy on abortion practices and, by extension, access. Aside from a means to terminate pregnancy, in different historical moments and geographical contexts, abortion has had various meanings and represented specific interests. A more recent manifestation is abortion as a complicated and contested subject of public debate. My dissertation establishes what the public life of abortion looked like at the time of SA's transition and how this public life influenced the law and its legacy for reproductive rights and justice. Medical and legal experts, civil society organisations, and aborting women formed a core network of voices that informed South Africa's progressive law. These contexts and publics require interrogation because of how they constructed CTOP as permissive and liberal. The concomitant perceptions of rights, empowerment, and democratic participation overshadowed the tangible ways that CTOP restricts abortion access.